Woolworths Foods : high-end retail in tough economic times - Beswick, Claire; Mosala, Thabo ([London] : SAGE, 2016)
In February 2009, Julian Novak, Woolworths divisional director of food, announced a new strategy for the company's food division. The South African retail sector had been affected by the global economic downturn and conditions were grim. By August 2008, Woolworths Food had already shown a drop in market share. Novak's new strategy included drastic reductions in prices and a variety of special deals and discounts. It was essential to attract lost customers back into its shops. Would Woolworths be able to do this while maintaining its quality/value proposition?
Originally Published in: Beswick, C., & Mosala, T. (2013). Woolworths Food: High-end Retail in Tough Economic Times. WBS-2013-23. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Woolworths; Strategic planning -- Case studies